Digital Transformation and its Impact on Enterprise Systems in the Manufacturing Sector - Judijanto, Loso; Vandika, Arnes Yuli; Zulkifli, Zulkifli; Aprian, Syawal (Westscience Press, 2024)
Digital transformation has revolutionized the manufacturing sector by enhancing the capabilities of enterprise systems. This study investigates the impact of digital transformation initiatives on operational efficiency, system flexibility, and decision-making capabilities within manufacturing enterprises. A quantitative approach was employed, involving 60 manufacturing enterprises and using a structured questionnaire based on a Likert scale (1-5). The data were analyzed with SPSS version 25, revealing significant positive relationships between digital transformation and the performance of enterprise systems. Regression analysis showed that digital transformation initiatives explained 42% of the variance in operational efficiency, 34% in system flexibility, and 38% in decision-making capabilities. The findings provide valuable insights into the transformative potential of digital technologies and highlight practical strategies for overcoming implementation challenges. This study contributes to the understanding of digital transformation's role in optimizing enterprise systems within the manufacturing sector.